Telomere-to-telomere Phragmites australis reference genome assembly with a B chromosome provides insights into its evolution and polysaccharide biosynthesis - Jipeng Cui; Rui Wang; Ruoqing Gu; Minghui Chen; Ziyao Wang; Li Li; Jianming Hong; Suxia Cui (Communications Biology)
Abstract Phragmites australis is a globally distributed grass species (Poaceae) recognized for its vast biomass and exceptional environmental adaptability, making it an ideal model for studying wetland ecosystems and plant stress resilience. However, genomic resources for this species have been limited. In this study, we assembled a chromosome-level reference genome of P. australis containing one B chromosome. An explosion of LTR-RTs, centered on the Copia family, occurred during the late Pleistocene, driving the expansion of P. australis genome size and subgenomic differentiation. Comparative genomic analysis showed that P. australis underwent two whole gene duplication events, was segregated from Cleistogenes songorica at 34.6 Mya, and that 41.26% of the gene families underwent expansion. Based on multi-tissue transcriptomic data, we identified structural genes in the biosynthetic pathway of pharmacologically active Phragmitis rhizoma polysaccharides with essential roles in rhizome development. This study deepens our understanding of Arundinoideae evolution, genome dynamics, and the genetic basis of key traits, providing essential data and a genetic foundation for wetland restoration, bioenergy development, and plant stress.